CREB in the Pathophysiology of Cancer: Implications for Targeting Transcription Factors for Cancer Therapy - Sakamoto, Kathleen M. (2009)
Transcription factors are key regulators of the pattern of gene expression in a cell and directly control central processes such as proliferation, survival, self-renewal, and invasion. Given this critical role, the function of transcription factors is normally regulated closely, often through transient phosphorylation. Although transcription factors are not often directly modified by mutations in cancer cells, they frequently become activated constitutively through mutations affecting “upstream” pathways. By continually driving the expression of key target genes, these oncogenic transcription factors play a central role in tumor pathogenesis. One such transcription factor is the cAMP-regulatory element-binding protein (CREB), which can be activated through phosphorylation by a number of kinases, including Akt, p90Rsk, protein kinase A, and calcium/calmodulin-dependent kinases and regulates genes whose deregulated expression promotes oncogenesis, including cyclins, Bcl-2 family members, and Egr-1. CREB is overexpressed and constitutively phosphorylated in a number of forms of human cancer, including acute myeloid leukemia (AML) and non – small cell lung cancer, and appears to play a direct role in disease pathogenesis and prognosis. Although transcription factors have not been a central focus of drug development, recent advances suggest that CREB and other such proteins may be worthwhile targets for cancer therapy.